2021
DOI: 10.1002/advs.202100606
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase‐Like Protein 14 Attenuates Mitochondrial Antiviral Signaling Protein Expression to Negatively Regulate Antiviral Immunity via N6‐methyladenosine Modification

Abstract: Mitochondrial antiviral signaling (MAVS) protein is the core signaling adaptor in the RNA signaling pathway. Thus, appropriate regulation of MAVS expression is essential for antiviral immunity against RNA virus infection. However, the regulation of MAVS expression at the mRNA level especially at the post transcriptional level is not well-defined. Here, it is reported that the MAVS mRNA undergoes N 6 -methyladenosine (m 6 A) modification through methyltransferase-like protein 14 (METTL14), which leads to a fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…These effectors work together dynamically to regulate the m 6 A modification process [ 12 ]. METTL14 is a vital m6A methylase that can form a heterodimeric methyltransferase complex with METTL3, and the METTL3–14 complex interacts with WTAP to catalyze the m 6 A modification of mammalian mRNA [ 13 , 14 ]. METTL14 has also been shown to play a vital role in many cancers.…”
Section: Introductionmentioning
confidence: 99%
“…These effectors work together dynamically to regulate the m 6 A modification process [ 12 ]. METTL14 is a vital m6A methylase that can form a heterodimeric methyltransferase complex with METTL3, and the METTL3–14 complex interacts with WTAP to catalyze the m 6 A modification of mammalian mRNA [ 13 , 14 ]. METTL14 has also been shown to play a vital role in many cancers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mRNAs of IFN-β and IFN-α, genes encoding the main cytokines that drive the type I interferon response, are m 6 A-modified and are stabilized following the depletion of METTL3 or METTL14, leading to increases in type I IFN expression and ISG induction. 1 , 31 Consequently, another study illustrated that the m 6 A reader YTHDF3 also restrains the type I IFN response and ISG expression in an m 6 A-independent way. 32 In addition, some results suggested that m 6 A modification interrupts the RIG-I and TLR innate immune activation pathway, and that nucleotide modifications with similar chemical structures may be organized into classes, which contribute to avoiding innate immune response.…”
Section: Discussionmentioning
confidence: 98%
“…METTL14 negatively regulated the production of a variety of cytokines in response to Sendai virus (SeV), by regulating the methylation of mitochondrial antiviral signaling (MAVS). 154 Therefore, it will be helpful to understand the role of m 6 A modification in the immune response during virus infection by studying how m 6 A regulates immune cell biology and immune molecules.…”
Section: Discussionmentioning
confidence: 99%